Visual preference of aesthetic quality for Permanent Forest Reserve in urban Klang Valley, Malaysia - Alsammrraie, Riyadh Mundher Sameen (2024)
Malaysia has experienced significant forest cover loss due to logging and urban development, particularly in urban areas. Although legislation for Permanent Forest Reserves (PFRs) exists, it lacks inclusivity, especially considering visual aesthetics as a crucial component of forest preservation. This omission has created gaps in public engagement, cultural appreciation, and emotional connections with these natural spaces, reducing the perceived value of PFRs among the public and policymakers and increasing the risk of degradation. This study addresses this gap by establishing a visual aesthetic quality assessment framework specifically tailored to PFRs in Klang Valley, Malaysia, using a converging approach that integrates public preferences and expert opinions. The framework involves two complementary approaches: the perception approach and the expert approach. The perception approach identifies suitable variables using the Participant-Generated Image (PGI) method, where participants capture images of visually appealing scenes, which are then classified by content. The expert approach determines the importance and weight of each variable through expert surveys and the Analytical Hierarchy Process (AHP). This study provides valuable insights into assessing and enhancing urban forests to meet local communities' aesthetic expectations by identifying key variables and evaluating their significance and weight. The resulting framework uniquely measures visual aesthetic quality by considering variables with different weightings rather than assuming equal importance for all variables. As the first comprehensive framework to assess visual aesthetics with variable weightings, it offers a practical tool for sustainable management and planning, helping to protect areas with high aesthetic value and suggesting improvements for those with lower appeal. Ultimately, the study's findings support a more inclusive conservation strategy that emphasizes aesthetics, ensuring the framework is comprehensive and adaptable to the diverse aesthetic needs of urban populations in Malaysia.